Religious Moderation Values in Siger Lampung Symbol - Setiawati, Rini; Rolando, Dede Mercy (KALAM, 2023)
This study aims to examine the values contained in Siger as a symbol of the people of Lampung Province and the effectiveness of these values in the concept of religious moderation. This research method is descriptive qualitative with the type of literature review. The analysis of this study uses Pierce's semiotic analysis and the concept of Quraish Shihab's moderation. The results of the research as a whole, Siger has the values contained in it in the form of the philosophy of the Lampung people or Piil Pesenggiri which is supported by 4 solid pillars including Juluk Beadek, Nemui Nyimah, Nengah Nyappur and Sakai Sambaian. This Lampung people's philosophy of life also refers to the Quraish Shihab's concept of Religious Moderation by presenting several pillars including Tawazun (Balance), Is (Justice), Tasamuh (Tolerance), Tawassuth (middle attitude) and Shura (deliberation). So, in religious moderation, it can be said that the visualization of Siger is a complete “package” that will enrich social life and also serve as a unifying tool for the plurality of Lampung society.